Вплив додавання екзомодифікованих вуглецевих наносфер на структурування в етанольних моторних паливах - Polunkin, E.A.; Pyliavskyi, V.S.; Gaidai, O.O.; Melnykova, S.L.; Spaska, O.A.; Matveeva, I. V. (V.P. Kukhar Institute of Bioorganic Chemistry and Petrochemistry of the National Academy of Sciences of Ukraine, 2021)
The work is devoted to elucidation of a general mechanism of action of exomodified carbon nanospheres (CNOs – Brn nanoonions) on different physicochemical and chemmotological properties of ethanol motor fuels. The formation of supramolecular solvate groups in organic media is explained by the participation of different forces of intermolecular interaction, the main of which are polarization and orientation, as well as donor-acceptor forces of interaction of nanospheres with the environment.The concept of creation in an organic medium of solvation formations - domains, the size of which, determined by the method of photon correlation laser spectroscopy, varies from 21 to 1000 nm, depending on the chemical nature of the solvent - is proposed and substantiated. For ethanol, the size of such formations was ~ 400 nm, which significantly exceeds the size of individual particles of the additive. It is established that to improve the operational characteristics of ethanol fuel it is enough to introduce low concentrations (10-3 - 10-2 %, wt.) of synthesized brominated nanoparticles.It is shown that the change of the microheterogeneous structure of fuels affects the change of its physicochemical and operational characteristics: the dielectric constant and hydrophobicity of the medium decrease, the saturated vapor pressure increases, which improves the starting properties of the fuel; hydrophobization of the environment helps to reduce the corrosive properties of ethanol fuel per unit, as a result of which additional introduction of a corrosion inhibitor is not required; the bearing capacity of the fuel in the presence of brominated nanoparticles increases by 1.5 times compared to the base fuel with a corresponding decrease in damage to the metal surface of the friction pairs.It is the rearrangement of the secondary supramolecular structure of fuels in the presence of brominated carbon nanospheres that explains the multifunctionality of their influence on the physicochemical and chemmotological properties of ethanol motor fuels.